Tingkat Pengetahuan Penanganan Cedera Olahraga Metode PRICES pada Timnas Basket U16 Putri - Mohammad Kamal Fakih Emami; Indra Himawan Susanto; Heri Wahyudi; Roy Januardi Irawan (Mutiara Pendidikan dan Olahraga, 2026)
This study aims to determine the level of knowledge of U16 women's national team athletes regarding injury management using the PRICES (Protect, Rest, Ice, Compression, Elevation, Support) method to improve athlete safety.. The study used a quantitative descriptive method with a cross-sectional approach. Data were collected through a Google Form questionnaire with 21 athletes as subjects. Data were classified using the Guttman scale and a dichotomous scale, then converted into a five-criteria scale. The data were processed using SPSS 22. The average score obtained was 136.81 with the lowest score being 117 and the highest score being 150. There were 8 (38.10%) subjects in the very high category, 10 (47.62%) subjects in the high category, and 3 (14.29%) subjects in the moderate category. These results indicate that the average subject's knowledge of the PRICES method is in the high or fairly good category. This indicates that most athletes have understood the basic principles of PRICES. An integrated educational program and practical simulation are needed in routine training to ensure that all athletes are able to apply the PRICES method quickly, precisely, and effectively when an injury occurs.